Ca ions chelation, collagen I incorporation and 3D bionic PLGA/PCL electrospun architecture to enhance osteogenic differentiation. (15th January 2021) - Zhou, Xuefeng; Cheng, Xi; Xing, Danlei; Ge, Qi; Li, Yan; Luan, Xianghong; Gu, Ning; Qian, Yunzhu
Abstract: Bioactive synthetic scaffolds with 3D porous structure are the most attractive materials among various guided bone regeneration membranes. However, its osteogenic potential is still insufficient. This study was aimed to develop a Calcium surface-anchored Collagen I-PLGA/PCL scaffolds (PP/COL I-pDA-Ca) with enhanced osteogenicity. PP/COL I-pDA-Ca was electrospun from a collagen I-blended PLGA/PCL matrix and then modified by the chelation of Ca-ions via mussel-inspired polydopamine coating. PLGA/PCL, PLGA/PCL-polydopamine, PLGA/PCL-pDA chelated by Ca-ions were used as controls. Osteogenic effects of the scaffolds were examined using MC3T3-E1 cell culture. PP/COL I-pDA-Ca maintained 3D porous architecture with interconnected pores formed by randomly-oriented filamentous fibers and MC3T3-E1 cells cultured on it for 12 h or 24 h were more stretched and spread than those on the controls. PP/COL I-pDA-Ca significantly upregulated α10, α11 and β1 integrin expression after 48 h culture. ALP activity, OCN, OSX, BMP2 and RUNX2 expression of MC3T3-E1 cells cultured on PP/COL I-pDA-Ca scaffolds for 7 and 14 days were substantially enhanced when compared to controls ( p  < 0.05). The pDA-based Ca chelation, COL I incorporation and 3D bionic structure promoted cell adhesion and osteogenic differentiation of MC3T3-E1 cells. This novel PP/COL I-pDA-Ca scaffolds is an attractive alternative for guided bone regeneration. Graphical abstract: Unlabelled Image Highlights: Collagen I-incorporated PLGA/PCL matrix was electrospun into 3D scaffolds. ECM-like architecture chelated by Ca ions via polydopamine coating for local delivery. Chelated-Calcium synergistically with collagen I promoted osteogenesis.